2011
DOI: 10.1177/0194599811423008
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Inferior Turbinate Reduction

Abstract: This long-term evaluation showed that radiofrequency treatment for allergic or nonallergic inferior turbinate hypertrophy appeared to provide improvement in olfaction, decrease nasal resistances, and have subjective benefits, maintained 2 years after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…Reduction of the inferior turbinates can be performed using different surgical techniques including total or partial inferior turbinectomy (PIT), lateral outfracture, microdebrider submucosal resection, laser-assisted turbinate reduction, argon plasma surgery, cryosurgery, treatment with infrared light, vidian neurectomy, chemical or electrical coagulation and radiofrequency volume turbinate reduction (RFVTR) 12 - 14 . The literature 12 - 15 provides considerable evidence for the efficacy of "hot surgery" in adults with symptomatic, inferior turbinate hypertrophy, with a significant increase in use of these techniques in the past decade. Important adverse effects of these techniques are likely the consequence of the heat generated by the power applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of the inferior turbinates can be performed using different surgical techniques including total or partial inferior turbinectomy (PIT), lateral outfracture, microdebrider submucosal resection, laser-assisted turbinate reduction, argon plasma surgery, cryosurgery, treatment with infrared light, vidian neurectomy, chemical or electrical coagulation and radiofrequency volume turbinate reduction (RFVTR) 12 - 14 . The literature 12 - 15 provides considerable evidence for the efficacy of "hot surgery" in adults with symptomatic, inferior turbinate hypertrophy, with a significant increase in use of these techniques in the past decade. Important adverse effects of these techniques are likely the consequence of the heat generated by the power applied.…”
Section: Discussionmentioning
confidence: 99%
“…Porter et al 27 in a small series showed that after two-years of follow-up there was no significant return of symptoms compared to evaluation at 6 months. Garzaro et al 12 evaluated patients at 2 months and 2 years after the surgical procedure using the "Sniffin' Sticks" test battery and the NOSE scale. Long-term evaluation showed that radiofrequency treatment for allergic or non-allergic inferior turbinate hypertrophy appeared to provide improvement in olfaction, decrease in nasal resistance and had subjective benefits that were maintained at 2 years after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Anwendung von Laser, Radiofrequenz und Shaver (Mikrodebrider) ermöglicht die Entfernung von submukosalen Geweben, wobei die Nasenschleimhaut intakt bleibt. Diese Methoden sind bei jungen Patienten wirksam und sollten auch bei älteren Patienten, insbesondere bei den antikoagulierten Patienten, vorteilhaft sein, bedürfen aber weiterer Forschung [6,12,16,17]. Unter den sehr alten Probanden sind lediglich 3 Studienteilnehmer mit oralen Antikoagulanzien aus der Gruppe der Vitamin-K-Antagonisten behandelt worden.…”
Section: Perspektiven Der Zukünftigen Forschungunclassified
“…Außerdem führt sie oft zum retrograden Sekretfluss (Postnasal-Drip-Syndrom -PNDS). Sie bewirkt auch eine Verschlechterung des Geruchssinns sowie der Geschmacksfunktion [3][4][5][6]. Wenn die genannten Symptome sich nicht durch therapeutische Maßnahmen wie Nasenduschen oder die Applikation von kortisonhaltigem Nasenspray positiv beeinflussen lassen, ergibt sich die Indikation für eine Nasenmuschelverkleinerung (Muschelplastik) [7,8].…”
Section: Introductionunclassified